OUTBREAK OF CHIKUNGUNYA VIRUS IN KARACHI, PAKISTAN - Sahibzada, Haafsa Arshad; Khurshid, Zohaib; Khan, Rabia Sannam; Zafar, Muhammad Sohail; Siddiqi, Khalid Mahmood (Journal of Ayub Medical College Abbottabad, 2018)
In this report, aim is to highlight the recent outbreak of Chikungunya virus in Karachi, the largest city of Pakistan. Chikungunya virus is transmitted by infected Aedes mosquitoes. Firstly, described as an outbreak in southern Tanzania in 1952 and later spread in Africa, Asia, Europe, and Pacific and Indian Oceans. In late 2016, the virus has been reported to cause severe morbidity and fatality among patients reporting to the local government hospital in Malir region of Karachi. Patients came to emergency ward with complaints of fever, skin rashes, fatigue and joint pain. To improve the existing knowledge and current epidemic in this area we reported the causes, sign & symptoms, precautions and treatment measures for the control from this virus spreading in mass gatherings. In addition, self-awareness, preventive measures implementation by public health officials in response to reports of Chikungunya virus will help to evaluate the outbreak settings. Keywords: Chikungunya virus; fever; skin rashes; joint pain; headache